1973
DOI: 10.1159/000230944
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin – An Important Allergen in Dog Epithelia Extracts

Abstract: Allergens from dog serum and extracts of dog hair, dandruff and skin scrapings were studied with respect to some physico-chemical and immunological properties. Serum albumin was found to be an important allergen present in high concentration in epithelia extracts. At least one additional serum protein was found to be a potent allergen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
2

Year Published

1975
1975
1993
1993

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 4 publications
1
27
2
Order By: Relevance
“…Immunoelectrophoretic and immunodiffusion analysis showed the presence of cat serum albumin. This serum protein could be responsible on the allerginicity of this frac tion and numerous reports indicate that albumin is an important allergen in horse [11] and dog [12] epithelia and to a lesser extent in cat extracts [2,4], The fraction with a mean molecular weight of 40.000 was resolved in two peaks of activity. One of them was associated with the protein band of pi 3.5.…”
Section: Discussionmentioning
confidence: 91%
“…Immunoelectrophoretic and immunodiffusion analysis showed the presence of cat serum albumin. This serum protein could be responsible on the allerginicity of this frac tion and numerous reports indicate that albumin is an important allergen in horse [11] and dog [12] epithelia and to a lesser extent in cat extracts [2,4], The fraction with a mean molecular weight of 40.000 was resolved in two peaks of activity. One of them was associated with the protein band of pi 3.5.…”
Section: Discussionmentioning
confidence: 91%
“…Dog dander antigen is quite heteroge neous and may contain several important antigenic components [6,7]. This factor along with the reported variability of poten cy and composition of commercially availa ble dog dander extracts would appear to make clinical use of this antigen extract somewhat difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Loewenstein's general studies of mammalian allergens [1] revealed several dog allergens, Uhlin et al [2] demon strated 24 antigens, whereas Ford et al [3] lergens in dog hair/dander extracts. Some of these aller gens have been identified as serum components, like albu min (Ag3) and y-globulin (Ag23) (2], By means of gel filtration, two components around 28 kD were character ised by Yman et al [4] in dog dander extracts. Recently, a major allergen (Agl3) was purified by Schou et al [5] re vealing a molecular weight (MW) of 25 kD on SDS-PAGE and 22 kD by HPLC gel filtration.…”
Section: Introductionmentioning
confidence: 99%